Experimental Phase Relations in Altered Oceanic Crust: Implications for Carbon Recycling at Subduction Zones. (2nd April 2018) - Martin, Laure A J; Hermann, Jörg
ABSTRACT: The phase relationships in altered mafic oceanic crust (K2 O, CO2 and H2 O bearing) have been investigated to constrain and quantify the processes of carbon transfer from the slab to the mantle wedge at subduction zones. We report experiments at 2·5–4·5 GPa and 700–900°C in which gas in the experimental charges is analysed by gas chromatography to constrain the volatile composition of the aqueous fluid or hydrous melt. A phengite-bearing epidote-eclogite with dolomite and/or magnesite is stable at subsolidus conditions. The wet solidus at f O2 of NNO (nickel–nickel oxide) was found between 700 and 750°C at 2·5–3·5 GPa and 800–850°C at 4·5 GPa, similar to the CO2 -free systems. This observation indicates a low amount of CO2 in the aqueous fluid phase at the wet solidus, in agreement with a measured X (CO2 ) of 0·059 ± 0·003 at 3 GPa, 700°C and 0·038 ± 0·003 at 3·5 GPa, 700°C. Experiments performed at higher f O2, using either an oxidized starting material or a Re–ReO2 buffer, resulted in a shift of the solidus to higher temperatures. Higher f O2 results in a higher X (CO2 ) in the aqueous fluid and the reduced water activity leads to a shift in the solidus to higher temperatures. Above the solidus, both textural observations and analyses of the gas enclosed in the capsule suggest that CO2 solubility in the silicate melt increases with increasing P – T conditions. At 4·5 GPa, more than 70% of carbonate at 850°C and 100% at 900°C was dissolved in the hydrous silicate melt. From textural observation it is not clear whether the high carbon content of the melt is related to an increased solubility of carbonate in the hydrous silicate melt or reflects an immiscible carbonatite melt. In any case, partial melting of altered oceanic crust at moderately oxidizing conditions (NNO) and pressures >4 GPa provides an efficient means for the transfer of carbon from the slab to the mantle wedge in intermediate to hot subduction zones. Significant amounts of subducted carbon can thus be brought back to the atmosphere via arc magmatism on relatively short time scales of less than 10 Myr.